2012
DOI: 10.5402/2012/345927
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Silage Inoculant on Silage Quality, Aerobic Stability, and Meat Production on Farm Scale

Abstract: The effect of inoculation on nutrient content, fermentation, aerobic stability, and beef cattle performance for whole-plant corn silage treated with a commercial product (blend of homo- and heterofermentative lactic acid bacteria, BSM, blend of Enterococcus faecium, Lactobacillus plantarum, and Lactobacillus brevis, DSM numbers 3530, 19457, and 23231, resp.), was compared to a control treatment with no silage additives (CT). The material had a DM of 323 g/kg, crude protein, and water-soluble carbohydrate conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…These results may be explained due to increase NDF content with supplemented additives to silage (as already reported in Table 1). However, the present finding is not in line with Acosta Aragon et al [38] who noted that whole crop corn silage treated with BSM (blend of homo-and heterofermentative lactic acid bacteria) has higher digestible and metabolizable energy than untreated silage. Our results confirmed the findings of Saricicek and Kilic [39] which showed that alfalfa silage treated with formic acid salts has lower ME than untreated control.…”
Section: In Vitro Intestinal Utilizable Crude Protein and Metabolizabcontrasting
confidence: 99%
“…These results may be explained due to increase NDF content with supplemented additives to silage (as already reported in Table 1). However, the present finding is not in line with Acosta Aragon et al [38] who noted that whole crop corn silage treated with BSM (blend of homo-and heterofermentative lactic acid bacteria) has higher digestible and metabolizable energy than untreated silage. Our results confirmed the findings of Saricicek and Kilic [39] which showed that alfalfa silage treated with formic acid salts has lower ME than untreated control.…”
Section: In Vitro Intestinal Utilizable Crude Protein and Metabolizabcontrasting
confidence: 99%
“…The ratio of ammoniacal nitrogen to total nitrogen in silage treated with acetic acid was significantly lower (p<0.05) than that of negative control over 30-90 days, suggesting that proteolysis was reduced by lowering plant enzyme activity or inhibiting undesirable microorganisms with the addition of acetic acid, potentially reducing the number of yeasts that cause spoilage in the presence of air. Some authors have described the benefits of the inhibition of spoilage organisms (37), demonstrating that lowered pH value in ensiled forage can effectively inhibit proteolysis because plant enzymes are quickly inactivated under these conditions (15). The ratio of ammoniacal nitrogen to total nitrogen in silage treated with formic acid, on average, was significantly higher (p<0.05) than that of negative control when stored between 90 and 170 days due to the higher pH values and weakened inhibitory effects, but ammonium content in all five silages was lower than the recommended value of 10 % of total nitrogen, indicating good silage, which demonstrated that the total nitrogen or crude protein in silages were well preserved (38).…”
Section: Dynamic Analysis Of the Fermentation Quality During 170 Daysmentioning
confidence: 99%
“…Better silage means better hygiene and therefore improvements in animal performance can be expected. The results of a trial discussed below give an example of how milk production can be improved [45]. In the trial, mixed grass-legume sward wilted for 6 -8 hours to 320 g DM/ kg (174 g of crude protein/ kg DM; 6.68 MJ NEL/ kg DM) was ensiled.…”
Section: The Use Of Silage Inoculants In Milk Productionmentioning
confidence: 99%
“…In spite of the sometimes controversial results, several trials have shown advantages from their use, reflected in better silage quality, aerobic stability and animal performance. The results of a trial conducted by [64] will be discussed in detail in the following paragraphs.…”
Section: The Use Of Silage Inoculants In Meat Productionmentioning
confidence: 99%